DEVELOPMENT OF A MOBILE APPLICATION FOR MONITORING THE EFFICIENCY OF ELECTRICITY USE - KHUDYI, ANDRII; YUSKEVYCH, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The development of information technologies is starting to pick up pace. If a few years ago innovations appeared every six months, and then once a year, now every day developers present new and new solutions for current problems. The field of saving natural resources also does not stand still. Standardization of emission norms, resource consumption leads to the emergence of clear environmental frameworks, without compliance with which products will not be allowed on the general market. Thus, the trend towards environmental protection is gaining a global scale and every day wins the hearts of more and more supporters. The paper describes the development of a mobile application for monitoring the efficiency of electricity use for daily industrial use. The goals of the application’s functioning have been formulated. A system for automatically collecting and displaying statistics on all electricity consumers has been implemented. The issue of saving electricity is also urgent. As exhaustible resources decrease, electricity becomes more expensive to produce. A large number of appliances consume quite a lot of electricity. Without her participation, the work of technology is impossible. Therefore, this leads to energy savings, or even use when needed. To develop a mobile-based system for monitoring the efficiency of electricity use were used the following technologies / tools: • Development Environment – xCode; • Language – JavaScript, TypeScript; • Database management system - mongoDB; • GUI – React, ReactNative; • Testing environment – iPhone Simulator, Android Studio. As a result was developed information system for monitoring the efficiency of electricity use. The object of the study is the process of creating a mobile application for monitoring the efficiency of electricity use. The subject of the research is the creation of a mobile application, the work of which will consist of collecting data from a specially designed and configured sensor and displaying it on the screen of a mobile phone.